Oral administration of docosahexaenoic acid activates the GDNF-MAPK-CERB pathway in hippocampus of natural aged rat. (September 2013) - Jiang, Li-He; Yan, Shi; Wang, Jin; Liang, Qiu-yun
Abstract Context: Docosahexaenoic acid (DHA) is one of the critical fatty acids for optimal health, which affect the expression of nerve growth factor and brain-derived neurotrophic factor in brain. Objective: This study investigates whether DHA supplementation affects lipid peroxidation and activates the glial-derived neurotrophic factor (GDNF)-mitogen-activated protein kinase pathway (MAPK pathway) in hippocampus of natural aged rat. Materials and methods: Rats were randomly divided into four groups; DHA was orally administered at 80 and 160 mg/kg/day to 24-month female rats for 50 days. The antioxidant parameters and GDNF-GDNF family receptor α-1 (GFRα1)-tyrosine-protein kinase receptor (RET)-MAPK-cyclic AMP response element-binding protein (CERB) pathway were assayed in natural aged rat's hippocampus. Results and discussion: The results demonstrated that DHA supplementation significantly increased the activities of superoxide dismutase (SOD) by 37.39 and 57.69%, glutathione peroxidase (GSH-Px) by 27.62 and 32.57% decreased TBARS level by 28.49 and 49.05%, respectively, but did not significantly affect catalase (CAT), in hippocampus, when compared with the aged group. DHA supplementation in diet resulted in an increase of DHA level in hippocampus. Furthermore, we found that DHA supplementation markedly increased the levels of GDNF and GFRα1 and the phosphorylation of RET, and led to the activation of the MAPK pathway in hippocampus tissue. Conclusion: DHA supplementation can change fatty acids composition, improve antioxidant parameters and activate the GDNF-MAPK pathway in natural aged rat's hippocampus.